Survival after resection of cutaneous adnexal carcinomas with eccrine differentiation: Risk factors and trends in outcomes. Issue 1 (16th May 2013) - Avraham, Jacob B.; Villines, Dana; Maker, Vijay K.; August, Carey; Maker, Ajay V.
Abstract Background Current staging systems do not specifically address cutaneous adnexal carcinomas with eccrine differentiation. Due to their rarity, prognosis and management strategies are not well established. A population‐based study was performed to determine prognostic factors and survival. Methods Patients diagnosed with cutaneous adnexal carcinomas with eccrine differentiation were identified using the surveillance, epidemiology, and end results population‐based cancer registry. Associations between risk factors, treatment modalities, and survival were calculated using logistical regression, Kaplan–Meier estimates and log‐rank analysis. Results The incidence of distinct eccrine subtypes was determined within 1, 045 patients with cutaneous adnexal tumors containing eccrine differentiation. All‐cause 5‐year survival (OS) was 82%, while age‐adjusted survival was 94%. Patients with microcystic adnexal carcinoma had improved OS (90%) compared to patients with hidradenocarcinoma (74%), spiradenocarcinoma (77%), porocarcinoma (79%), and eccrine adenocarcinoma (81%). The majority of patients were treated with surgical excision and a small subset with surgery plus radiation, with similar OS. Patients with well‐to‐moderately differentiated tumors demonstrated improved OS compared to those with poorly differentiated/anaplastic disease. Conclusions Histological subtype and grade were associated with survival, and should be specified in biopsies and excised specimens. Surgical excision is appropriate, and the addition of adjuvant radiation may not be associated with survival. These results highlight survival data and high‐risk prognostic factors that warrant prospective validation, and may augment current staging systems. J. Surg. Oncol. 2013 108:57–62. © 2013 Wiley Periodicals, Inc.